"Communists in the Church": the role of progressive Catholics in encouraging popular participation in the Sisal Region of Bahia in the last years of the 20th century - Miranda, Cristian Barreto de (Revista Crítica Histórica, 2019)
This paper aims at presenting a brief discussion about the role of lay religious people, considered progressive Catholics, in encouraging popular participation in the socio-political decisions in the city of Conceição do Coité – located in the Sisal region of Bahia – in the final years of the twentieth century. These Catholics’ political actions contributed to downsize a political framework linked to the dictatorial regime and to strengthen the Popular Church in Conceição do Coité’s community. The theoretical-methodological perspective guiding this analysis works on the same assumptions adopted by the political historiography’s new approach and it is articulated with sources of several natures.